Optimizing and validating the technical infrastructure of a novel tele-cystoscopy system. (October 2016) - Hougen, Helen Y; Lobo, Jennifer M; Corey, Thomas; Jones, Randy; Rheuban, Karen; Schenkman, Noah S; Krupski, Tracey L
Introduction: Bladder cancer is the most costly malignancy to manage per capita due to the technical nature and intensity of follow-up. There are few urologists in rural areas, often necessitating that patients travel hours to receive follow-up care multiple times per year. We plan to train registered nurses and allied health professionals to perform cystoscopies which are monitored and interpreted in real-time by board-certified urologists. The key is to ensure optimal picture resolution to guarantee this technology is not inferior to traditional cystoscopy. Our objective was to develop the technical infrastructure needed for a tele-cystoscopy system through assessment of the transmitted video quality using expert reviewers and crowd-sourcing. Methods: All combinations of the tele-cystoscopy system were systematically tested using a single Thiel cadaver. The videos were reviewed by expert urologists and general reviewers using a crowd-sourcing website. The video quality responses were assessed to determine concordance between each set of reviewers, and to determine the optimal equipment that should be selected for the tele-cystoscopy system. Results: Of eight equipment combinations, only two were of high enough quality to be appropriate for medical use. We found there to be strong concordance of responses between the expert and crowd-sourced responses. The trade-offs between cost and tele-cystoscopy system component quality were compared with efficiency frontiers to elucidate the optimal system. Discussion: We created and tested the feasibility of a tele-cystoscopy system that was deemed suitable for medical diagnosis by a group of experts. We further validated tele-cystoscopy video quality using both experts and recently validated crowd-sourcing.